Of rice, fish, ducks and humans - Dai Rong; Xue Dayuan (The UNESCO Courier, 2019)
The Dong people, a Chinese ethnic minority who have lived for thousands of years in Congjiang county, in the heart of Guizhou province, were ecologists before their time. Centuries ago, they invented an agricultural system that we would term “green” today – producing organic food while preserving the stability and diversity of local ecosystems. The “Rice-Fish-Duck” Symbiotic System is the direct result of their ancestral wisdom.